Valuation of the decline in fish catch in Sarangani Bay due to organic aid nutrient pollution - Lofranco, Christy Amor P.
This study was an attempt to quantify the decline in marine municipal fsh catch in Sarangani Bay as a result of pollution. It focused on the organic and nutrient type of pollution from agricultural industries particularly livestock and poultry sector. Regression analysis was used to assess the relationship between pollutant loads (BOD and NO3) and fisheries productivity in the Bay. Statistics showed that the volume of production was negatively affected by the amount of pollutant discharges. Both variables were significant at five percent level. Results also showed that P/608.35 million was the loss to the fisheries sector in a span of 12 years, from 1990-2002.
Thesis, Undergraduate (BS Economics) -- U. P. in Mindanao